Comprehensive performance evaluation of a high-throughput automated system for pathogen nucleic acid detection in clinical settings - Lu, Rongqi; Zhang, Rui; Liu, Yali (Frontiers in Microbiology, 2025)
ObjectiveThis study evaluates the clinical performance of a high-throughput automated molecular detection system and proposes a comprehensive and standardized performance validation framework to address gaps in existing methodologies and provide a robust reference for future evaluations.MethodsPerformance was validated for EBV DNA, HCMV DNA, and RSV RNA using clinical samples at various concentrations, along with WHO and national reference standards. The validation included concordance rate, accuracy, linearity, precision, limit of detection, interference testing, cross-reactivity, and carryover contamination.ResultsThe positive, negative, and overall concordance rates for EBV DNA, HCMV DNA, and RSV RNA were all 100%. Both intra-assay and inter-assay precision showed coefficients of variation (CV) below 5%. The linear correlation coefficient (| r|) for EBV DNA and HCMV DNA was ≥ 0.98, demonstrating excellent linearity. The limits of detection (LoD) were 10 IU/mL for EBV DNA and HCMV DNA, and 200 copies/mL for RSV RNA. Both interference and cross-reactivity assessments met the CLSI EP07 standards, and no carryover contamination was observed.ConclusionThe system demonstrated excellent performance in terms of concordance, accuracy, precision, linearity, interference testing, and cross-reactivity. It is highly suited for large-scale pathogen screening and routine nucleic acid testing in clinical laboratories, both for qualitative and quantitative analyses. Additionally, this study introduces a comprehensive and standardized performance validation framework that addresses critical gaps in existing methodologies, offering a robust foundation for the rigorous evaluation of diagnostic systems and serving as a valuable reference for future research.